Now or Later? : The Political Economy of Public Investment in Democracies - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2015)
This paper explores the impact of political and institutional variables on public investment. Working with a sample of 80 presidential and parliamentary democracies between 1975 and 2012, we find that the rate of growth of public investment is higher at the beginning of electoral cycles and decelerates thereafter. The peak in public investment growth occurs between 21 and 25 months before elections. Cabinet ideology and government fragmentation influence the size of investment booms. More parties in government are associated with smaller increases in public investment while left-wing cabinets are associated with higher sustained increases in investment. Stronger institutions help attenuate the impact of elections on investment, but available information is insufficient to draw definitive conclusions.